Influence of breed, milk diet and slaughter weight on carcass traits of suckling kids from seven Spanish breeds - Panea, B. (2013)
This experiment aimed to describe the influence of production system on the following characteristics from seven Spanish goat breeds: carcass weight, dressing percentage, head weight, viscera weight, kidney fat weight, fatness score, carcass length, leg length, rump perimeter, rump width, kidney fat colour and tissue composition of shoulder. Experiment involved 201 male, single-birth suckling kids from five meat and two dairy breeds. Animals from meat breeds were slaughtered at two targets carcass weights (light, 4 kg; heavy, 7 kg). In dairy breeds, half of the animals were reared with dam’s milk and the other half with a milk replacer and all of them were slaughtered at light weight (4 kg). Statistics consisted in two GLM, means for each variable, a PCA to study relationships between variables and a discriminant analysis to compare breeds. In dairy breeds, breed had greater influence than milk diet, with breed effect being particularly strong for kids that were fed with natural milk. In meat breeds, slaughter weight was more important than breed and many significant interactions were found between both effects. All carcass traits were closely related to each other and to slaughter weight. Slaughter weight was also positively related to dressing percentage and to fatness degree. Discriminant analysis explained 76.1% of variability and separated dairy breeds, with well-fattened, medium-shaped carcasses, from meat breeds, with good conformations and medium fatness degrees. Hence, carcass traits were able to group breeds by diary or meat type.